Tuberculosis Infection Mimicking Brain Metastatic Malignancy Lesions in an Elderly Male - Dimitrios Anyfantakis; Ageliki Damianaki; Maria Kokosi; Emmanouil K. Symvoulakis; Serafim Kastanakis (Case Reports in Infectious Diseases)
An 83-year-old Caucasian Greek man was referred by his general practitioner to the emergency department of the general hospital in Crete because of seizures and agitation. His past medical history was negative for any neurological or medical condition. Electroencephalogram showed a bradyarrhythmic theta activity, without evidence of any focal or other specific abnormality. Magnetic resonance imaging of the brain demonstrated a number of diffuse nodular lesions and moderate perivascular edema. An axillary lymph node fine needle aspiration cytology suggested a granulomatous lymphadenitis along with signs of tuberculous infiltration. Tuberculin skin test was positive. We report a rare case of extrapulmonary tuberculosis mimicking brain metastatic lesions.